Higher diversity of Brucella canis in Latin America, according to an MLVA_13 Bc analysis - Boeri, Eduardo Jorge; Ruybal, Paula; Dominguez, María Luz; Fernandez, Natalia Mercedes; Becker, Paula; Elena, Sebastián; Escobar, Gabriela Ileana; Ayala, Sandra Marcela; Hasan, Deborah Beatriz; Trangoni, Marcos David (Elsevier, 2023)
Brucella canis is the main causative agent of canine brucellosis, which affects domestic and wild canids and leads to clinical signs and symptoms of the reproductive and locomotor systems. Owing to the scarce information on this pathogen, here we addressed the genetic diversity of the circulating strains of this species in Argentina by following an MVLA_13 Bc scheme. The analyzed sample set consisted of 101 strains of B. canis isolates collected between 2006 and 2020 from canines of the Autonomous City of Buenos Aires (CABA) and other regions of Argentina, as well as 235 isolates from North America. The analysis yielded 336 variants (Hunter–Gaston Diversity Index, HGDI equal to 1.0) showing high diversity on a global scale. The analysis of the six most variable markers also reveled high diversity and allowed further analysis regarding variant relationships. Although the diversity obtained using both schemes (all or the 6 most variable markers) was higher for the Latin American than for the North American strains, we cannot discard that this was due to biases in the sampling methodology or to the different health policies employed in these regions regarding the management of infected individuals. Altogether, the Argentine circulating strains are genetically diverse, but with no apparent geographical association. The markers used in the MLVA_13 Bc are variable and highly useful for the evaluation of outbreaks. Furthermore, the reduced panel of 6 markers (MLVA_6 Bc) proposed in this study is convenient for the study of B. canis strain diversity.